Lesbian rites : symbolic acts and the power of community - Laird, Joan (New York : Harrington Park Press, 2003)
Fonds Suzan Daniel (FSD)
Ook uitgegeven als Journal of Lesbian Studies 07(2003) 2
Engels
Monografie